(untitled) (INNOVATIVE ECONOMY, 2021)
Shust O.A., Paska I.M., Hrynchuk Yu.S. IMPROVING MEASURES OF STATE STIMULATION OF INVESTMENT ACTIVITY IN INCREASING SOIL FERTILITY Purpose. The aim of the article is the development of scientifically substantiated proposals on state stimulation of the process of investment of farms of the corporate sector of the agrarian economy in increasing the fertility of agricultural lands in the conditions of transformation processes of land relations. Methodology of research. In conducting the study, its methodological and theoretical basis is the dialectical method of cognition and a systematic approach to the study of the fundamental provisions of economics for investment activities in the agricultural sector of Ukraine. A set of special methods of economic research was used in the research process. The conclusions of the research are formulated with the help of abstract and logical method. The method of theoretical generalization was used in the critical analysis of the results of research by domestic scientists on the substantiation of economic incentives to increase the fertility of agricultural land. Results. The economic levers of the state regulation of nature use in the production of agricultural products are substantiated, which provides for the use of a comprehensive combination of payments for the rational use of agricultural land and penalties for reducing soil fertility. Originality. A scientific approach to the reproduction of land resources in agricultural enterprises is proposed, which is based on a set of organizational and economic tools for socially responsible activities, in particular: development of programs for targeted use of agricultural land and providing them with appropriate funding, calculation of land tax and other changes in soil quality, which will increase the fertility of agricultural land. Practical value. The implementation of the proposed economic stimulus measures will help increase the rational land use of agricultural producers and improve soil quality. The use of the proposed measures is possible only with a well-established system of agrochemical assessment of agricultural land. Key words: fertility, capital investments, agricultural lands, state, agricultural commodity producers.